2013
DOI: 10.1002/emmm.201201773
|View full text |Cite
|
Sign up to set email alerts
|

A ntimicrobial peptides and gut microbiota in homeostasis and pathology

Abstract: We survive because we adapted to a world of microorganisms. All our epithelial surfaces participate in keeping up an effective barrier against microbes while not initiating ongoing inflammatory processes and risking collateral damage to the host. Major players in this scenario are antimicrobial peptides (AMPs). Such broad-spectrum innate antibiotics are in part produced by specialized cells but also widely sourced from all epithelia as well as circulating inflammatory cells. AMPs belong to an ancient defense s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
194
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 294 publications
(196 citation statements)
references
References 209 publications
(241 reference statements)
1
194
0
1
Order By: Relevance
“…This physical barrier consists of enterocytes tightly connected by intracellular junctions [43]. Depending on the level of injury, enterocytes also secrete cytokines and chemokines, which trigger the inflammatory response, as a second line of defense against the luminal contents [7,44,45], resulting in infiltration of neutrophils, macrophages and other immune cells to the site of intestinal damage or inflammation [4]. …”
Section: Discussionmentioning
confidence: 99%
“…This physical barrier consists of enterocytes tightly connected by intracellular junctions [43]. Depending on the level of injury, enterocytes also secrete cytokines and chemokines, which trigger the inflammatory response, as a second line of defense against the luminal contents [7,44,45], resulting in infiltration of neutrophils, macrophages and other immune cells to the site of intestinal damage or inflammation [4]. …”
Section: Discussionmentioning
confidence: 99%
“…However, recent work has instead suggested that defensins interact with Lipid II and thereby interrupt bacterial cell wall synthesis [15] . Depending on their intramolecular disulfide bonding pattern, defensins present in the gut are subdivided into α-and ÎČ-defensins [16] . Of the six α-defensins identified in Paneth cells so far, human defensin-5 (HD5) and human defensin-6 (HD6) are of particular importance for the small intestinal immune system.…”
Section: Antimicrobial Peptidesmentioning
confidence: 99%
“…For example, specialized Paneth cells in the small intestine store and secrete various antimicrobial effectors (e.g., lysozyme, phospholipase A2 group IIA or REGIII); but their most abundant products are the α-defensins human defensin (HD) 5 and HD6. Both α-defensins and ÎČ-defensins are bactericidal, with activity against Gram-negative and Gram-positive bacteria (Bevins and Salzman, 2011; Ostaff et al, 2013). It was reported that human gut microbes from all dominant phyla are resistant to high levels of Cationic AMPs polymyxin B.…”
Section: Pathways In Which the Host Shapes Microbesmentioning
confidence: 99%